2017
DOI: 10.1039/c7ra07722j
|View full text |Cite
|
Sign up to set email alerts
|

Plasma-assisted and thermal atomic layer deposition of electrochemically active Li2CO3

Abstract: Growth per cycle as a function of process table temperature for both plasma-assisted (squares) and thermal (circles) ALD processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
37
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 36 publications
6
37
1
Order By: Relevance
“…33 A sputtering procedure was adopted to investigate the stoichiometry of the film. In contrast to our previous XPS studies of Li 2 CO 3 , 34 the stoichiometry of the films did not change during depth profiling. The obtained LiF stoichiometry of the film is 54.4 at% Li, 44.3 at% F, 0.3 at% C and 0.4 at% O.…”
Section: Ald Processcontrasting
confidence: 99%
“…33 A sputtering procedure was adopted to investigate the stoichiometry of the film. In contrast to our previous XPS studies of Li 2 CO 3 , 34 the stoichiometry of the films did not change during depth profiling. The obtained LiF stoichiometry of the film is 54.4 at% Li, 44.3 at% F, 0.3 at% C and 0.4 at% O.…”
Section: Ald Processcontrasting
confidence: 99%
“…The calculated ionic conductivity of ITO layer estimated to be 1.43 × 10 −9 S cm −1 from Equation (), σ=1ρ=1kA where σ is the ionic conductivity, ρ is the resistivity, k is the slope, and A is the active area of 1.05 cm 2 . This value is comparable with some of the lithium containing materials such as Li 2 CO 3 (≈1.0 × 10 −10 S cm −1 ) [ 33 ] and Li 3 PO 4 (≈1.4 × 10 −10 S cm −1 ), [ 34 ] indicating the appreciable ionic conductivity of this ALD ITO thin‐film.…”
Section: Resultssupporting
confidence: 75%
“…AR = aspect ratio. The stability window listed here is based on thermodynamic calculations reported by Richards et al [77] Electrolyte Material LixAlyS 3×10 −7 --Thermal [102] Li3BO3-Li2CO3 2×10 −6 -AR 13 (99%) Ozone [88] Li2CO3 ---Thermal [103] 10 −10 -AR 25 (80%) Thermal [104] 10 −10 -AR 25 (82%) Plasma [104] Towards full 3D thin-film batteries A recent step towards a full 3D TFB was published by Létiche et al, who showed a 3D TiO2 thin-film electrode coated with a Li3PO4 SSE film. [38] The structure and property of this 3D thin-film electrode is shown in Figure 8.…”
Section: Conformal Solid-state Electrolytesmentioning
confidence: 99%